Voices of Literature Academics Toward The Rise of AI-Generated Literature - Rahmat Setiawan; Sri Nurhidayah; Andi Karman (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The principle of this research is to explore the perspectives of literary academics on AI’s ability to create literary works. This type of research is qualitative and the approach in this research is a case study. There are 3 lecturers who are the subjects in the interview which is packaged in a forum group discussion which is also the data collection technique used in this study. The data in this study are statements from the subjects during the FGD and the data source is the transcript of the FGD. The analysis technique used in this research is thematic analysis. From the analysis, it is found that AI-Generated literary works provides multiple perspectives from literary academics: 1) Concerns about the impact of AI on literature; 2) AI’s potential to expand access to literature; 3) The need for collaboration between humans and AI; and 4) The need for regulation and ethics in the development of AI for literature. This research shows that literary academics have mixed views on the development of literature created with AI. They have concerns about the impact of AI on literary values and traditions, but they also see the potential for AI to expand access to literature. Literary academics emphasise the importance of collaboration between humans and AI in creating literature and the need for regulation and ethics in the development of AI for literature.